Assessing the sustainability of the blue swimming crab (Portunus pelagicus) on the Eastern Coast of Lampung: a holistic approach to conservation and resource stewardship - Yulianto, Herman; Ihsan, Yudi Nurul; Sumiarsa, Dadan; Ansari, Andrianto; Hendarmawan (Frontiers in Marine Science, 2024)
Increasing demand for blue swimming crabs due to their economic value and protein contained has significantly impacted their habitat and population. Sustainable management with a holistic approach is paramount to ensuring these marine resources' long-term viability. Here, we integrate ecological conservation, socioeconomic well-being, and governance principles to provide a comprehensive framework for formulating a policy framework for the sustainability management of Blue Swimming Crab in the Eastern Coast of Lampung. The research underscores the importance of mangrove areas as essential habitats for various aquatic biota, including the blue swimming crab, and emphasizes the need for proper mangrove management to ensure ecological integrity. Our research sheds light on the concerning issue of overexploitation, with an exploitation rate recorded at 0.71, necessitating immediate attention to prevent the depletion of crab stocks and maintain a healthy ecosystem. It highlights the need for continued efforts to preserve the mangrove ecosystem and ensure the sustainable management of the BSC fishery. Recommendations include technological interventions, clarified law enforcement, and holistic conservation strategies to ensure the resilience of BSC populations, the prosperity of local communities, and the preservation of vital coastal ecosystems. Government support, combined with active community participation, is vital to sustain the blue swimming crab fishery and protect the delicate balance between human activities and the natural environment.